Academics’ resistance to online learning during COVID-19, its antecedents and consequences: Lesson learned for the impacts on work-related outcomes - Rindi Ardika Melsalasa Sahputri; Martina Diah Purwaningsih; Naila Kamaliya; Septiana Sihombing; Sujarwoto Sujarwoto; Dia Agustia Salsabila (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
COVID-19 has resulted in a global shift toward online education. Rapid and unprecedented change resulted in organisational unreadiness and resistance to change. As a learning organisation, academia is expected to adapt swiftly to disruptive change; however, evidence mapping the outcomes of such change—particularly how resistance to change affects academic performance—remains limited, especially given the drastic shift in teaching delivery caused by the pandemic. This study thus aims to understand the impact of education institution management when organising change on lecturers' resistance and its implication for lecturers’ work-related outcomes (i.e., lecturer commitment, satisfaction, and performance). The instrument was a Google Forms questionnaire using Oreg's attitude toward change scale. Explanatory sequential mixed method design combining quantitative survey methodologies with a cross-sectional design and narrative analysis were used in this study. This study used convenience sampling which included one hundred and fifty-one lecturers from fifteen public universities in Indonesia. Partial least squares modelling (PLS-SEM) was used to test the quantitative analysis and thematic analysis was used to classify the qualitative finding. The results found that change-related information and intrinsic reward significantly affect lecturers’ resistance behaviour. Every component of resistance behaviour is also associated with lecturers’ commitment to organisation, satisfaction, and performance. This study contributes to fulfilling the research gap by providing evidence on how academics' or lecturers' responses to drastic change and its implication on their performance.